2023
DOI: 10.21608/ejhc.2023.279725
|View full text |Cite
|
Sign up to set email alerts
|

Risk Determinants of Incontinence associated dermatitis among Critically Ill Patients.

Abstract: Background: Keeping skin integrity functioning and skin barrier protection is an important aspect of nursing care. ICU patients are susceptible to various skin complications, such as pressure ulcers and moisture-related skin damage. Aim: This study aimed to pinpoint incontinence-associated dermatitis (IAD) risk determinants among ICU patients. Design: A prospective observational research design was conducted. Setting(s): Data collection was done in two general ICUs. Participants: A convenience sample of 200 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Studies were conducted in the United States ( n = 3), 35 , 36 , 37 China ( n = 3), 38 , 39 , 40 Brazil ( n = 1), 41 Australia (n = 1), 42 Spain (n = 1), 43 Belgium (n = 1), 44 Japan (n = 1) 45 and Egypt (n = 1). 46 Ten studies were prospective cohort studies, 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 one was retrospective 36 and one was a RCT. 44 Three studies were conducted in long‐term care facilities, 36 , 44 , 45 one in community care 35 and eight in intensive care units (ICUs).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies were conducted in the United States ( n = 3), 35 , 36 , 37 China ( n = 3), 38 , 39 , 40 Brazil ( n = 1), 41 Australia (n = 1), 42 Spain (n = 1), 43 Belgium (n = 1), 44 Japan (n = 1) 45 and Egypt (n = 1). 46 Ten studies were prospective cohort studies, 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 one was retrospective 36 and one was a RCT. 44 Three studies were conducted in long‐term care facilities, 36 , 44 , 45 one in community care 35 and eight in intensive care units (ICUs).…”
Section: Resultsmentioning
confidence: 99%
“… 44 Three studies were conducted in long‐term care facilities, 36 , 44 , 45 one in community care 35 and eight in intensive care units (ICUs). 37 , 38 , 39 , 40 , 41 , 42 , 43 , 46 Sample sizes ranged from 37 to 381 patients. Detailed descriptions of included studies are shown in Appendix S2 (Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations